Managing Curricular Innovation and Teacher Training: Bangladesh Perspective (IIUC Studies, 2016)
This study aims at finding out the necessity of teachers training to put into practice the LT(Communicative Language Teaching) based English textbooks (English for Today series i.e. EFT) in Bangladesh at school and college levels where Grammar-Translation-Literature based curriculum had been followed for decades. Using a mixed methods approach, I conducted the study by engaging the teacher participants in the questionnaire response, interviewing them, observing their classes and consulting different official reports and research findings. The study revealed that majority of our English teachers are not trained up at all to use these CLT textbooks though they feel that training might definitely skill them well and make them efficient enough to handle the newly designed EFT textbooks more effectively. It further revealed that even trained up teachers cannot create a truly communicative environment in the classroom as the existing testing system encourages students to memorize answers to some probable questions rather than engage them in communicative activities. This paper ends with some recommendations to overcome this existing hopeless situation.IIUC Studies Vol.12 December 2015: 09-26